Numeration-Based Teaching Materials on Algebra Shape Materials for Blended Learning - Safitra, M. David; Hapizah; Mulyono, Budi; Susanti, Ely (Mosharafa: Jurnal Pendidikan Matematika, 2023)
Kebutuhan bahan ajar diperlukan untuk meningkatkan efektifitas pembelajaran dan pemahaman peserta didik. Penelitian bertujuan menghasilkan bahan ajar berbasis numerasi materi bentuk aljabar untuk blended learning yang valid, praktis dan memiliki efek potensial terhadap kemampuan numerasi peserta didik. Teknik pengumpulan data adalah angket, tes dan wawancara. Sampel penelitian ini adalah 24 peserta didik kelas VII salah satu SMP Negeri di Palembang. Kevalidan bahan ajar dilihat dari aspek kelayakan isi, bahasa, tampilan, serta komentar dan saran dari hasil uji coba one-to-one. Kepraktisan bahan ajar dilihat dari angket. Skor rata-rata kevalidan bahan ajar adalah 74,77 dengan kriteria cukup valid atau layak digunakan dengan revisi. Sedangkan skor rata-rata kepraktisan bahan ajar adalah 87,08 dengan kriteria sangat praktis. Bahan ajar yang dikembangkan memiliki efek potensial terhadap kemampuan numerasi dilihat dari hasil tes 8 peserta didik terkategori sangat baik, 9 peserta didik terkategori baik, 4 peserta didik terkategori sedang dan 3 peserta didik terkategori kurang. The need for teaching materials is needed to help improve effective learning and student understanding. This study aims to produce numeration-based teaching materials in algebraic forms for blended learning that are valid, practical and have a potential effect on students' numeracy abilities. Data collection techniques used are questionnaires, tests and interviews. The sample of this research was 24 class VII students of one of the state Junior High School in Palembang. The validity of teaching materials was seen from the aspects of content feasibility, language feasibility, display feasibility, also comments and suggestions from the results of one-to-one trials. The practicality of teaching materials can be seen from the questionnaire. The average score for the validity of teaching materials is 74.77 with the criteria being quite valid or suitable for use with revisions. While the average practicality score of teaching materials is 87.08 with very practical criteria. The developed teaching materials also have a potential effect on numeracy skills as seen from the test results with 8 students in the very good category, 9 students in the good category, 4 students in the moderate category and 3 students in the poor category.